Clinical and mechanism advances of neuronal intranuclear inclusion disease - Liu, Yueqi; Li, Hao; Liu, Xuan; Wang, Bin; Yang, Hao; Wan, Bo; Sun, Miao; Xu, Xingshun (Frontiers in Aging Neuroscience, 2022)
Due to the high clinical heterogeneity of neuronal intranuclear inclusion disease (NIID), it is easy to misdiagnose this condition and is considered to be a rare progressive neurodegenerative disease. More evidence demonstrates that NIID involves not only the central nervous system but also multiple systems of the body and shows a variety of symptoms, which makes a clinical diagnosis of NIID more difficult. This review summarizes the clinical symptoms in different systems and demonstrates that NIID is a multiple-system intranuclear inclusion disease. In addition, the core triad symptoms in the central nervous system, such as dementia, parkinsonism, and psychiatric symptoms, are proposed as an important clue for the clinical diagnosis of NIID. Recent studies have demonstrated that expanded GGC repeats in the 5′-untranslated region of the NOTCH2NLC gene are the cause of NIID. The genetic advances and possible underlying mechanisms of NIID (expanded GGC repeat-induced DNA damage, RNA toxicity, and polyglycine-NOTCH2NLC protein toxicity) are briefly summarized in this review. Interestingly, inflammatory cell infiltration and inflammation were observed in the affected tissues of patients with NIID. As a downstream pathological process of NIID, inflammation could be a therapeutic target for NIID.